1988
DOI: 10.1111/j.1751-1097.1988.tb02729.x
|View full text |Cite
|
Sign up to set email alerts
|

CHEMICALLY MODIFIED PHOTOSYNTHETIC BACTERIAL REACTION CENTERS: CIRCULAR DICHROISM, RAMAN RESONANCE, LOW TEMPERATURE ABSORPTION, FLUORESCENCE AND ODMR SPECTRA AND POLYPEPTIDE COMPOSITION OF BOROHYDRIDE TREATED REACTION CENTERS FROM Rhodobacter sphaeroides R26

Abstract: Abstract-Reaction centers from Rhodobacter sphaeroides have been modified by treatment with sodium borohydride similar to the original procedure [Ditson el al., Biochim. Biophys. Acta 766, 623 (1984)], and investigated spectroscopically and by gel electrophoresis.(1) Low temperature (1.2 K) absorption, fluorescence, absorption-and fluorescence-detected ODMR, and microwave-induced singlet-triplet absorption difference spectra (MIA) suggest that the treatment produces a spectroscopically homogeneous preparation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

1988
1988
1991
1991

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…It was generally accepted (but see [22]), that treatment with borohydride removed about 50% of the monomeric bacteriochlorophylls absorbing at 802 nm. From kinetic and spectroscopic evidence it had been suggested that the 'inactive' BChl q (BB) , is reduced at the 3-acetyl group by this treatment, and then subsequently lost from the remaining complex [9,21,[23][24][25]. As a side reaction, partial cleavage of the M-subunit has been observed in the case of Rb.…”
Section: Introductionmentioning
confidence: 99%
“…It was generally accepted (but see [22]), that treatment with borohydride removed about 50% of the monomeric bacteriochlorophylls absorbing at 802 nm. From kinetic and spectroscopic evidence it had been suggested that the 'inactive' BChl q (BB) , is reduced at the 3-acetyl group by this treatment, and then subsequently lost from the remaining complex [9,21,[23][24][25]. As a side reaction, partial cleavage of the M-subunit has been observed in the case of Rb.…”
Section: Introductionmentioning
confidence: 99%
“…
Incubation of photosynthetic reaction centers from Rhodobucter sphaeroides R26 with exogenous lY-OH-bacteriochlorophyll ar or aoo according to Scheer et al (1987) results in the exchange of endogenous bacteriochlorophyll ar. The exchange amounts to 5 50% according to HPLC analysis, corresponding to a complete replacement of the 'monomeric' bacteriochlorophylls, Bu and Br, by exogenous pigment.
…”
mentioning
confidence: 99%
“…However, this Interpretation has been challenged by the finding of (1) an unchanged pigment composition in BH4 -treated RCs (Struck et al, 1992a), (2) a tetrapyrrolic pigment at the B" site in the poorly resolved X-ray structure (J. Allen, personal communication, 1991), and (3) at least partial proteolysis of the M subunit (Beese et al, 1987). The BH4~ reduction also leads to distinet changes in Chlorophyll proteins of higher plants, but these changes have not yet been investigated at a molecular level ).…”
Section: "Double Mutant H-l153-s/h-m180-s Binds Two Bchl a At Ba1imentioning
confidence: 99%
“…This Option was indicated by the finding of Walter et al (1979) that different esterüying alcohols are present in Bphea and Bchla of Rs. rubrum RCs, in conjunetion with the finding that these RCs did not discriminate strongly between pigments bearing phytol or geranylgeraniol (Scheer et al, 1987;Beese, 1989;Struck, 1991). The mutagenesis experiments (Table 0 suggest the same mechanism if the exchange of the amino acid next to the central N-4 cavity at any one of the positions is not assumed to bestow these sites indiscriminately with dechelafase activities.…”
mentioning
confidence: 97%
See 1 more Smart Citation